106 THE HYBRID POSITION IS SUPERIOR TO THE PRONE POSITION FOR THORACOSCOPIC ESOPHAGECTOMY WITH UPPER MEDIASTINAL LYMPHADENECTOMY. (14th September 2020) - Kikuchi, H; Hiramatsu, Y; Soneda, W; Kawata, S; Hirotsu, A; Matsumoto, T; Kamiya, K; Takeuchi, H
Abstract:  : Thoracoscopic esophagectomy (TE) is becoming a common surgical method for esophageal cancer. TE is performed with the patient the left lateral decubitus position, prone position, or hybrid position combining the left lateral decubitus and prone positions. However, only few studies have compared the clinical utility of these TE positions. Methods: In our institute, we introduced TE in the prone position (prone TE) in 2014, and have performed TE in the hybrid position (hybrid TE) since March 2017. The present study compared the short-term outcomes of prone TE versus hybrid TE. One-hundred-and-three patients with esophageal or esophagogastric junction cancer who underwent TE between March 2014 and December 2019 were included. Patients were divided into those who underwent prone TE (prone TE group; n = 43) and those who underwent hybrid TE (hybrid TE group; n = 60). Clinicopathological data were retrospectively reviewed and compared between groups. Results: There were no differences between groups in age, tumor histology, and tumor location. Compared with the hybrid TE group, the prone TE group had a smaller tumor depth (P < 0.001), lower grade of lymph node metastasis (P = 0.003), and less severe tumor stage (P = 0.001). The operation time for the thoracoscopic procedure was shorter in the hybrid TE group (318.9 vs 249.2 min, P = 0.002). The rate of recurrent laryngeal nerve paralysis (Clavien-Dindo grade I–III) was significantly lower in the hybrid TE group (41.9% vs 11.7%, P < 0.001), whereas there were no differences between groups in the rates of anastomotic leakage, atelectasis, or pneumonia. Conclusion: The most significant differences between prone TE and hybrid TE involved the upper mediastinal procedures. In hybrid TE, the motion of the assistant's forceps causes less interference with the operative field, and the angle at which the operator's forceps approach the upper mediastinal lymph nodes enables the maintenance of appropriate traction. These advantages of hybrid TE appeared to result in a shorter operation time and less recurrent laryngeal nerve paralysis compared with prone TE.